METODE BIMBINGAN PENYULUHAN AGAMA ISLAM DALAM MENGATASI REMAJA PUTUS SEKOLAH DI DESA TELAGA BARU KECAMATAN LASALIMU SULAWESI TENGGARA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study discusses the method of guidance and counseling on Islam in dealing with school dropouts in Telaga Baru Village, Lasalimu District, Southeast Sulawesi. This study aims to: 1). This is to determine the factors that cause teenagers to drop out of school in Telaga Baru Village, Lasalimu District, Southeast Sulawesi. 2). This is to find out the methods of Islamic guidance and counseling in dealing with teenagers dropping out of school in Telaga Baru Village, Lasalimu District, Southeast Sulawesi. 3) Supporting and inhibiting factors for Islamic extension agents in dealing with teenagers dropping out of school in Telaga Baru Village, Lasalimu District, Southeast Sulawesi. The results showed that: 1). Teenagers dropping out of school in Telaga Baru Village are increasing due to the lack of educational infrastructure and community awareness of the importance of education, the weak economy of the community, and the lack of interest and desire from adolescents to go to school. 2). The method applied by Islamic extension agents in overcoming school dropouts is a persuasive approach to adolescents and parents to establish good cooperation, build public awareness of the importance of education through socialization and lectures.